Modeling the dynamics of landscapes and livelihoods in Malinau District, Indonesia - Suwarno, A.; Campbell, Bruce M. (Modelling and Simulation Society of Australia and New Zealand, 2005)
The complex dynamic interactions between land resources and society have to be taken into account when planning land use and managing land resources. Simulation models and participatory modeling can be ideal tools to improve our understanding of these complex interactions. For several decades, land use in Malinau district was dictated by the central government through the allocation of land to agriculture, timber concessions and mining companies. Now, with a policy of decentralization in place, district governments have a greater say in the allocation of land use. As a part of the district government development programs to increase district revenue, several forest areas are likely to be allocated for plantation production, but the proposed creation of a “conservation district” will require some level of forest protection. Using a combination of empirical data and stakeholder’s participation, a computer model using STELLA software was developed to investigate long term land use, district revenue and livelihood dynamics. Indonesian forests are globally important biodiversity hotspots. However, we hypothesize that land use changes, in which forests are converted to plantation and other intensive land uses, are to the benefit of most key stakeholders that can drive these changes. The modeling results show that the imperative for large-scale development (i.e. plantation and other intensive land use systems) is enormous, as such systems will yield significant benefits to local authorities and local people. While there will undoubtedly be losers with such development (e.g. hunter-gatherers relying on non-timber forest products; those who are displaced by plantation expansion; the conservation lobby), the current incentives are likely to drive forest conversion.